Programma: 22 april Amsterdam Hard Sucks Elvis; 23 april Jadis; 25 april Blue Aeroplanes; 27 april Dionne Farris
Programma: 22 april Amsterdam Hard Sucks Elvis; 23 april Jadis; 25 april Blue Aeroplanes; 27 april Dionne Farris.